he Science of Mountains - Louise Spilsbury (Bharat Little Prodigy Books, 2023)
For all those young scientists who aren't mountain climbers, this lively look at high-altitude ecosystems takes us to the highest peaks to learn about the amazing interactions between plants and animals of the mountains. From high-flying bees that pollinate the flowers to lumbering bears who spread seeds for plant growth, mountain organisms need each other in a multitude of ways. Flowcharts throughout this brightly designed book elucidate important concepts such as mountain food chains and the effects of climate change on mountain ecosystems.
Keywords: Where We Are in Place and Time -- -Settlements